Random rank-dependent expected utility - Nail Kashaev; Victor H. Aguiar (Games, 2022)
We present a novel characterization of random rank-dependent expected utility for finite datasets and finite prizes. As a byproduct, we obtain a characterization of random expected utility that works for finite datasets. The test lends itself to statistical testing. We apply our test to an experimental dataset and find evidence against random expected utility, while random rank-dependent expected utility can explain the dataset.
Keywords: C50; C51; C52; C91; 330; expected utility; random utility; rank-dependent expected utility